Conceptualization of Marine Vocational Education from the Perspective of the Quran: A Thematic-Philosophical Analysis - Hakim, Bay Amri; Arief, Armai; Hariyadi, Muhammad (STKQ Al-Hikam Depok, 2025)
This article aims to examine and formulate the concept of maritime vocational education from a thematic-philosophical Qur’anic perspective. It responds to the lack of comprehensive approaches that integrate Qur’anic values with the needs of maritime vocational education. Using a qualitative method through library research, this study applies thematic exegesis and a normative-philosophical approach. The findings reveal that the Qur’an contains numerous references to the sea and its management, reflecting educational principles such as ecological responsibility, productive work, and fair, sustainable resource use. The study also formulates core philosophical values underlying maritime vocational education, including tawhid, justice, sustainability, integration of knowledge and action, and religious humanism. This conceptualization is proposed as a relevant educational model to develop maritime generations who are both technically competent and morally transformative. The findings offer a strategic alternative for developing vocational education rooted in divine revelation while being responsive to contemporary socio-ecological challenges.